Кислотна переестерифікація олій етанолом на твердофазних каталізаторах вуглецевої природи - Fedoryshyn, Olexandr S. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
The main advantages and disadvantages of solid-phase catalysts for transesterification reactions of oils with alcohols are analyzed. Tests of the sulfonated and phosphated solid - phase catalysts synthesized by us in the transesterification reaction of rapeseed oil with 96% ethanol in order to obtain biodiesel were carried out. The chemical resistance of sulfonated synthetic (S-SCS) and synthesized from natural raw materials (S-KAU) catalysts was compared. The reasons for low chemical resistance of sulfonated carbon-containing materials are determined. Synthetic S-SCS catalysts proved to be the least stable. Regeneration of phosphated samples was performed by washing the catalyst from oil residues and reaction products in a boiling solution of 0.1 M alkali, followed by repeated washing with distilled water to slightly alkaline pH. Then, after drying, the obtained material was used as a source for re-synthesis of the catalyst. The ethanolysis reaction was carried out in autoclaves under pressure at a temperature of 150-160oC with a process duration of 5-7 hours. The ratio of catalyst to starting oil was chosen 1:15 (g : ml). The oil-alcohol ratio was 3: 4, vol. The volume of the autoclave was 45 ml. The maximum conversion under these test conditions in the first cycle for sulfonated catalysts was 100%, and for phosphated - 94%. A carbon-containing catalyst on a ceramic support has been developed, which can be regenerated by firing the carbon-containing material and applying a new one. This catalyst showed the highest chemical resistance, withstanding 7 cycles, while the conversion fell by 14% (from 89 to 75%). For more efficient use of the catalyst, the scheme of flow-circulation installation of transesterification of oils and fats of biological origin with alcohols was proposed.